The effects of oxidizer-to-fuel ratio on some characteristics of a silver iodide pyrotechnic for cloud seeding - Jose, Wilfredo L. (1976)
With constant silver iodide content the oxidizer-to-fuel ratio of the pyrotechnic formulation is varied from 0.5 to 8 by weight. The temperature of reaction and the burning rate decrease as the ration is increased. The average smoke particle sizes are large for low rations and smaller but essentially constant for high ratios with a minimum exhibited between 3 and 2.5 The maximum threshold temperature of ice crystal formation is likewise between the ratios of 3 and 3.5.